Progress Toward an Early Social Indicator for Infants and Toddlers. (June 2021) - Greenwood, Charles R.; Carta, Judith J.; Schnitz, Alana G.; Higgins, Susan; Buzhardt, Jay; Walker, Dale; Jia, Fan; Irvin, Dwight
Measures of young children's social development are needed in the Multi-Tier System of Supports (MTSS) approach to early childhood. In 2004, we reported initial development of an observational measure of infants' and toddlers' social skills designed for early educators, the Early Social Indicator (ESI). Here, we report preliminary findings on the ESI's feasibility, sustainability, and sensitivity to growth in social engagement based on a large, multiyear sample of children in one early childhood program that agreed to pilot the measure. Results indicated that ESI use by program staff was sustained over a 5-year period. Program staff were reliable coding a range of children's positive and negative nonverbal and verbal social skills. However, staff were not reliable when coding the target of a child's social response when it was not the Adult play partner (i.e., the Peer, or Nondirected target). Results documented sensitivity to growth over time, dynamic patterns of change within and across key skills consistent with the typical course of social development, and moderation by children's home language and Individual Family Service Plan (IFSP) status. Implications are discussed.